IMPLEMENTATION OF EMPLOYMENT MANAGEMENT INFORMATION SYSTEMS IN THE GLOBAL EXELLENCE COURSE INSTITUTION - Fendi Hidayat (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2021)
Global Excellence Batam course institute (GE Batam) is a non-formal educational institution that has several course programs that have been trusted by the Batam community. To improve its institutional organization, GE Batam wants to implement a human resource management information system (HRIS). In this research, HRIS development will be carried out using a codeigniter framework then the system will be used. As a result, the HRIS implemented by GE Batam can run well and data can be stored in a database and can be managed easily.